Coccidiosis infection and growth performance of broilers in experimental trials: insights from a meta-analysis including modulating factors - Luís Filipe Villas Boas de Freitas; Nilva Kazue Sakomura; Matheus de Paula Reis; Alexandre Bonadiman Mariani; William Lambert; Ines Andretta; Marie-Pierre Létourneau-Montminy (Poultry Science, 2023)
ABSTRACT: An infection by protozoa Eimeria spp. can cause coccidiosis, which negatively affects broiler chicken performance and causes economic and production losses. To understand the effect of coccidiosis on broilers' performance, we evaluated the independent variables and their interactions on the severity of coccidiosis in broilers that cause variation (Δ) of average daily feed intake (ADFI), average daily gain (ADG), and gain per feed (G:F) of broiler chicks using a meta-analysis approach. A database of 55 papers describing 63 experiments was gathered; broilers were challenged by Eimeria species (E. acervulina, E. maxima, E. tenella, and mixed) and at least 2 variables among ADFI, ADG, and feed conversion ratio (FCR) were studied. The variation induced by the challenge was calculated relative to the control group of each experiment. The indirect factors evaluated were days postinfection (DPI), Eimeria type and dose, infection age (IA), bird's mean age in the analyzed period, genetic line, sex, and whether they were raised in a cage or a pen. Graphical, correlation, and variance analyses were performed to evaluate the form of the responses. Then, a linear plateau model was adjusted for each response variable as a function of DPI to determine the consequences of the disease on the variation of performance over time after infection. The impact of the infection challenge on the variation of performance vs. nonchallenge broilers was only impacted by DPI (P < 0.05). The adjustment of the data with the linear plateau model allows us to determine the host response to the coccidiosis disease at different stages. At 5 DPI (acute phase), ΔADFI, ΔADG, ΔG:F were of −19.0; −39.8, and −25.5, respectively. After almost 13 DPI birds achieved the recovery phase for all variables with Δ varying from −19 to −3.75% for ADFI, from −39.8 to −10.5% for ADG, and from −25.5 to −7.24% for G:F. The Eimeria impact was higher in ADG than ADFI in all periods due to Eimeria aggressive action form causing lesions in gut epithelial reducing the use of nutrients and energy. The results can be used as a quantitative approach to determine the consequences of Eimeria spp. on broiler performance.